1998
DOI: 10.2527/1998.7651469x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting forage indigestible NDF from lignin concentration.

Abstract: We used chemical composition and in vitro digestibility data from temperate and tropical forages to develop relationships between indices of lignification and forage indigestible NDF. Neutral detergent fiber indigestibility increased nonlinearly as the lignin concentration of the NDF increased. Differences in estimated indigestible NDF using equations developed for a specific forage class (C3 and C4 grasses and legumes) were small and are probably not biologically significant when compared to those estimated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
1
21

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 18 publications
(40 reference statements)
7
52
1
21
Order By: Relevance
“…The highest A fraction of corn stover could be explained by the lower NDF content across maturities. The highest B fraction for elephant-grass could be an indicator of higher potentially degradable fiber, which is usually negatively correlated with lignin/NDF (Traxler et al, 1998). However, in this study, the lignin/NDF content of elephant-grass was higher than in corn stover (Table 1).…”
Section: Dry Matter Degradabilitycontrasting
confidence: 50%
“…The highest A fraction of corn stover could be explained by the lower NDF content across maturities. The highest B fraction for elephant-grass could be an indicator of higher potentially degradable fiber, which is usually negatively correlated with lignin/NDF (Traxler et al, 1998). However, in this study, the lignin/NDF content of elephant-grass was higher than in corn stover (Table 1).…”
Section: Dry Matter Degradabilitycontrasting
confidence: 50%
“…The reason is that lignin has no substantial effect on the digestibility of cell solubles. Traxler et al (1998) agreed with our findings when they reported a better correlation between the indigestible residue of NDF and the lignin content of DMrather than the lignin content of NDF.…”
Section: Resultssupporting
confidence: 93%
“…Carbohydrate fraction C The equation representing the unavailable cell wall has been employed or cited by several researchers (Malafaia et al, 1998;Traxler et al, 1998;Ribeiro et al, 2001) and appears in the nutritional requirements for beef cattle (National Research Council, 2000). Other models for predicting energy and nutrient values of ruminant feeds also employ relationships between lignin and NDF, but using a 0.667 power (Weiss et al, 1992;Weiss, 1993 and1999).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the Cornell Net Carbohydrate and Protein System (CNCPS) nutritional model uses a lignin content that is 2.4 times lignin content of NDF to calculate the iNDF (Sniffen et al, 1992;Vieira et al, 2012), whereas iNDF is not considered by Dairy NRC (2001). This simple equation was originally based on long-term (60 to 90 days) methane yield on some waste materials, and then tested on several forages by Traxler et al (1998). As reported by these authors, the equation was able to correctly predict iNDF of the different forages.…”
Section: Discussionmentioning
confidence: 88%